Glioblastoma with Oligodendroglioma Component (GBM‐O): Molecular Genetic and Clinical Characteristics. (30th January 2013) - Appin, Christina L.; Gao, Jingjing; Chisolm, Candace; Torian, Mike; Alexis, Dianne; Vincentelli, Cristina; Schniederjan, Matthew J.; Hadjipanayis, Costas; Olson, Jeffrey J.; Hunter, Stephen; Hao, Chunhai; Brat, Daniel J.
Abstract Glioblastoma (GBM) is an aggressive primary brain tumor with an average survival of approximately 1 year. A recently recognized subtype, glioblastoma with oligodendroglioma component (GBM‐O), was designated by the World Health Organization (WHO) in 2007. We investigated GBM‐Os for their clinical and molecular characteristics as compared to other forms of GBM. Tissue samples were used to determine EGFR, PTEN, and 1p and 19q status by fluorescence in situ hybridization (FISH); p53 and mutant IDH1 protein expression by immunohistochemistry (IHC); and MGMT promoter status by methylation‐specific polymerase chain reaction (PCR). GBM‐Os accounted for 11.9% of all GBMs. GBM‐Os arose in younger patients compared to other forms of GBMs (50.7 years vs. 58.7 years, respectively), were more frequently secondary neoplasms, had a higher frequency of IDH1 mutations and had a lower frequency of PTEN deletions. Survival was longer in patients with GBM‐Os compared to those with other GBMs, with median survivals of 16.2 and 8.1 months, respectively. Most of the survival advantage for GBM‐O appeared to be associated with a younger age at presentation. Among patients with GBM‐O, younger age at presentation and 1p deletion were most significant in conferring prolonged survival. Thus, GBM‐O represents a subset of GBMs with distinctive morphologic, clinical and molecular characteristics.